(11-3.x)+(2.x-5)=(-22)^0 (8.x-17)-(9.x+23)=(-6)^2

(11-3.x)+(2.x-5)=(-22)^0
(8.x-17)-(9.x+23)=(-6)^2

2 bình luận về “(11-3.x)+(2.x-5)=(-22)^0 (8.x-17)-(9.x+23)=(-6)^2”

  1. (11-3.x)+(2.x-5)=(-22)^0
    11-3.x+2.x-5=1
    (11-5)-(3.x-2.x)=1
    6-x=1
    x=6-1
    x=5
    _Vậy : x=5.
    ——-
    (8.x-17)-(9.x+23)=(-6)^2
    8.x-17-9.x-23=36
    (8.x-9.x)-(17+23)=36
    -x-40=36
    -x=36+40
    -x=76
    x=-76
    _Vậy : x=-76.

    Trả lời
  2. Giải đáp + Lời giải và giải thích chi tiết:
     (11-3x) + (2x-5) = (-22)^0
      11 – 3x + 2x -5 = 1
       (-3x + 2x) = -11 + 5 +1
                   -x = -5
                => x = 5
         Vậy x = 5
    (8x – 17) – (9x +23) = (-6)^2
     8x – 17 – 9x – 23 = 36
       (8x – 9x) = 36 + 23 + 17
                -x = 76
                => x = -76
        Vậy x = -76 

    Trả lời

Viết một bình luận

Câu hỏi mới